COMPARATIVE ANALYSIS OF HANDWRITING: JUVENILES IN OBSERVATION HOMES VS. JUVENILES IN NGO’S AND SCHOOL (Journal of Forensic Medicine & Toxicology, 2025)
In this study, handwriting of individuals under the age of eighteen who reside in observation homes are compared to the handwriting of individuals selected from non governmental organisations and schools (NGOs). The study, conducted in Uttar Pradesh, India, involved 80 juveniles who were chosen from observation homes and an equal number who came from various schools and non-governmental organisations. A written consent was acquired to maintain privacy of participants. Handwriting samples were collected and analysed using established methodologies to identify patterns, variations, and potential indicators of socio-behavioural differences. The findings reveal significant disparities in handwriting styles and quality between juveniles in observation homes and those in NGOs and schools. The results show that there are significant gaps in educational achievement, mental health indicators and social integration among the observed groups. It is worth mentioning that those in the schools outdid those from the observation homes academically whereas psychological evaluations portrayed them as having worsened mental conditions. On the other hand, the NGO’s children have better social integration and support systems than their counterparts in observation homes. These results emphasize how much a juvenile’s environment affects its development and welfare. Additionally, they call for focused measures and
Keywords: evaluations; handwriting; environment